2020
DOI: 10.2147/mder.s260732
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Mechanical Impedance of the Human Skull via Direct Bone Conduction Implants</p>

Abstract: Point your SmartPhone at the code above. If you have a QR code reader, the video abstract will appear. Or use: https://youtu.be/zbv0NO6djwo Purpose: The mechanical skull impedance is used in the design of direct bone drive hearing systems. This impedance is also important for the design of skull simulators used in manufacturing, service, and fitting procedures of such devices. Patients and Methods: The skull impedance was measured in 45 patients (25 female and 20 male) who were using percutaneous bone conducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 16 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…Among the studies, different types of implants were used ( Table 1 ) but also different ways to attach to the implant, for example by screwing the transducer to the implant or by a snap-coupling. It has been shown that the connection between the transducer and the implant/skull introduces a compliance that can affect the high-frequency BC stimulation ( Hakansson et al, 2020 ). Since the impedance of the skull and the skull simulator used for calibration differ, and the connection to attach the BC transducer can be different between the skull and skull simulator, the high-frequency stimulation level can differ between the skull and the skull simulator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies, different types of implants were used ( Table 1 ) but also different ways to attach to the implant, for example by screwing the transducer to the implant or by a snap-coupling. It has been shown that the connection between the transducer and the implant/skull introduces a compliance that can affect the high-frequency BC stimulation ( Hakansson et al, 2020 ). Since the impedance of the skull and the skull simulator used for calibration differ, and the connection to attach the BC transducer can be different between the skull and skull simulator, the high-frequency stimulation level can differ between the skull and the skull simulator.…”
Section: Discussionmentioning
confidence: 99%
“…This computation indicated, due to a shift in the BC transducer's resonance frequency at around 400 Hz, up to 5 dB higher output levels on the human mastoid compared with the artificial mastoid at frequencies below 400 Hz and around 5 dB lower output levels on the human compared with the artificial mastoid at frequencies above 400 Hz (Surendran & Stenfelt, 2021). A similar computation based on the impedances of a BC implant and the skull simulator used to measure the output force of a BC transducer for skull attachment (Hakansson et al, 2020), indicated 2.5–5 dB higher output levels on the human implant compared with the skull simulator at frequencies below 1 kHz. At frequencies above 1 kHz, the output on the human implant was 2.5 dB lower than that measured on the skull simulator.…”
Section: Discussionmentioning
confidence: 99%
“…For a frequency band-specific interpretation of our results, it can be helpful to consider the categorization of mechanical point impedance ( 20 , 38 ). The skull impedance exhibits an antiresonance at around 150 Hz ( 20 , 37 ). Below this antiresonance, the mechanical point impedance is predominantly governed by the mass of the skull.…”
Section: Discussionmentioning
confidence: 99%
“…The temporal bone is a highly complex structure containing air cells and composed of different types of bone tissue, such as cortical bone, cancellous bone, and diploë, with varying densities ( 19 ). The transmission of energy from the transducer to the temporal bone should be influenced by the mechanical point impedance ( 20 ). Different bone column densities should therefore affect the local mechanical impedance as well as the impedance matching between the transducer and the skull.…”
Section: Introductionmentioning
confidence: 99%
“…However, the vibration does not propagate directly to the inner ear, but rather passes through the skull; it was thus important to measure the signal through the skull. We employed an artificial mastoid (type 4930; Brüel & Kjaer, Naerum, Denmark) commonly used to measure the forces of bone conduction devices [45], [46], [47], [48]. To this end, the coil vibration transducer was completely assembled including the titanium housing cap [Fig.…”
Section: Evaluation Of the Transducer Outputmentioning
confidence: 99%